2015
DOI: 10.1016/j.bmc.2015.04.082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of linker length in shape recognition of B∗ DNA by dimeric aminoglycosides

Abstract: DNA-protein recognition has shown us the importance of DNA shapes in the recognition process. Specific high-affinity targeting of DNA shapes by small molecules is desirable for many biological applications that involve regulation of DNA based processes. Here, the effect of linker length and rigidity on the affinity of a conjugated neomycin dimer for a specific DNA shape (B* form) AT-rich DNA was explored. Binding constants approximating 108 M−1 for optimal linker lengths of 18–19 atoms are reported herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…With the current increase in availability of both gene sequences and the knowledge of their functions in life‐forms ranging from bacteria to humans, there is clearly an unmet need for new, sequence‐specific, small‐molecule DNA probes . Significant variations in the cell‐uptake potential of molecular structures and pharmacokinetic differences will also require discovery and development of a diversity of different molecular systems for DNA recognition that do not currently exist …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the current increase in availability of both gene sequences and the knowledge of their functions in life‐forms ranging from bacteria to humans, there is clearly an unmet need for new, sequence‐specific, small‐molecule DNA probes . Significant variations in the cell‐uptake potential of molecular structures and pharmacokinetic differences will also require discovery and development of a diversity of different molecular systems for DNA recognition that do not currently exist …”
Section: Introductionmentioning
confidence: 99%
“…[7,9,15] Significant variations in the cell-uptake potentialo fm olecular structuresa nd pharmacokinetic differences will also require discoverya nd development of ad iversity of different molecular systems for DNA recognition that do not currently exist. [16][17][18][19]…”
Section: Introductionmentioning
confidence: 99%
“…Unlike some other ligand screening methods which mandate the presence of a fluorophore in the ligand to be screened, this assay can be used to screen both fluorescent as well as non-fluorescent molecules binding to the nucleic acids. The utility of this assay has been demonstrated by many laboratories which have used both canonical and non-canonical nucleic acid structures of biological interest (Monchaud et al, 2006;Kumar et al, , 2015Kellish et al, 2014). More importantly several applications of this assay have been shown to be useful in discovering G-quadruplex binding ligands (Monchaud et al, 2006).…”
Section: Fluorescence Intercalator Displacement Experimentsmentioning
confidence: 99%
“…A complete thermodynamic study of neomycin dimer 115 binding to a B-DNA sequence revealed that the first binding event (the high affinity site) is entropically driven and that the ionic strength dependence of the binding is highly dependent on the electrolytic contribution [ 194 ]. The neomycin dimers also displayed length dependent shape recognition of the B-DNA [ 195 ].…”
Section: Reviewmentioning
confidence: 99%